2021
DOI: 10.1001/jamadermatol.2021.1136
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Physical and Psychological Outcomes of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis

Abstract: IMPORTANCEStevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is known to cause multiple end-organ complications in its acute phase, but less is known about the long-term association with patients' mental health and quality of life.OBJECTIVE To examine the chronic physical and psychological sequelae affecting patients with SJS/TEN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…Whilst there is a dearth of studies relating to the psychological impact of SJS/TEN on patients’ lives, the existing studies acknowledges the range of psychological effects on patients’ well-being such as anxiety, depression and PTSD [ 14 – 19 , 21 , 22 ]. The psychological sequelae of burns are well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there is a dearth of studies relating to the psychological impact of SJS/TEN on patients’ lives, the existing studies acknowledges the range of psychological effects on patients’ well-being such as anxiety, depression and PTSD [ 14 – 19 , 21 , 22 ]. The psychological sequelae of burns are well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some SJS/TEN patients sustain feelings of distress and reveal Post-Traumatic Stress (PTS) symptoms [ 18 , 21 ], while others experienced anxiety and depression [ 17 – 19 ]. A recent study of SJS/TEN survivors (n = 121) found that 43.3% of participants screened positive for anxiety, 53.3% presented with a positive depression screen, and 19.5% had positive screening for PTS [ 22 ]. Dodiuk-Gad et al [ 18 ] in their study of SJS/TEN survivors (n = 17), found that even though many of the individuals presented with psychological sequelae only four were assessed by a mental health practitioner following diagnosis with SJS/TEN.…”
Section: Introductionmentioning
confidence: 99%
“…Les nécrolyses épidermiques toxiques (Stevens-Johnson et Lyell) ont des séquelles physiques à long terme dans plus de 50 % des cas (cutanées, oculaires et buccales) et des séquelles psychologiques fréquentes, syndromes dépressifs, anxiété, syndrome post-traumatique et la peur des nouveaux médicaments [ 62 ]. De nouveaux responsables de nécrolyse épidermique ont été identifiés dans la base de données VIGIBASE de l’Organisation mondiale de la santé (OMS) (pharmacovigilance de 131 pays).…”
Section: Peau Et Médicamentsunclassified
“…The most common sequalae are skin and mucosal problems. Hoffman et al reported the prevalence of physical sequalae relevant to SJS/TEN, including cutaneous problems (84.3%), ocular problems (59.5%), and oral mucosal problems (50.8%) [ 5 ]. Skin hyperpigmentation, scarring, hair loss, and nail dystrophy are also common.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological problems including anxiety, depression, and post-traumatic stress disorder have also been reported in these patients. According to a study, the physical and psychological sequelae of SJS/TEN caused lack of ability to work in 28.2% patients, and 68.1% and 30.0% patients were fearful or avoided taking medications, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%